Reconstruction of Restitution as an Additional Punishment for Victims of Criminal Acts - Aprilianda, Nurini; Mufatikhatul Farikhah; Ryan Ilham Fibriansyah; Nadhilah A. Kadir (Universitas Brawijaya, 2024)
Victims of criminal acts, as individuals who suffer harm, deserve comprehensive protection, particularly in the process of recovering their losses. The enactment of the National Criminal Code has recognised this need by including compensation as an additional form of punishment. However, the current framework has significant shortcomings. Since this additional punishment is not mandatory, victims are not guaranteed compensation, undermining the principle of justice. This study explores the need to reform the existing system to ensure fair and effective restitution for victims. Based on normative research utilising a statutory approach and interpretative analysis, the findings suggest that positioning criminal compensation as a primary form of punishment within the National Criminal Code would better serve justice. By elevating criminal compensation to a primary punishment, the system would provide victims with greater certainty in securing recovery from the perpetrator.